1990
DOI: 10.1002/apmc.1990.051760127
|View full text |Cite
|
Sign up to set email alerts
|

Properties and role of benzoquinone imines in polymer stabilization

Abstract: Quinone imines are formed from aromatic amine antidegradants as a consequence of chemical transformations of the latter during the stabilization of hydrocarbon polymers. Quinone imines are deep coloured compounds and contribute to the antidegradant activity of the parent amines. The main interest is devoted to benzoquinone diimines (BQDI), generated from N,N '‐disubstituted 1,4‐phenylenediamines (PD). BQDI are antioxidants in unsaturated hydrocarbons, undergo hydrolytic deamination, addition and cyclization re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…We also found that halogenated hydroxy-l,4-benzoquinones were formed in a mixture with other compounds during the oxidation of trihalogenated pyrocatechols. Accordingly, 4-chloroand 4,5-dichloropyrocatechol yielded 2,5-dihydroxy-l,4-benzoquinone [ 141 , that is, the same product as that arising during the oxidation of pyrocatechol alone in an alkaline medium [15,16]. Besides quinoid compounds which are also the product of a reaction between tetrahalogenated pyrocatechols and tert-butylhydroperoxide, deeper oxidation leads to the formation, in a small amount, of the cleavage products of the aromatic ring; oxalic acid was identified here.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that halogenated hydroxy-l,4-benzoquinones were formed in a mixture with other compounds during the oxidation of trihalogenated pyrocatechols. Accordingly, 4-chloroand 4,5-dichloropyrocatechol yielded 2,5-dihydroxy-l,4-benzoquinone [ 141 , that is, the same product as that arising during the oxidation of pyrocatechol alone in an alkaline medium [15,16]. Besides quinoid compounds which are also the product of a reaction between tetrahalogenated pyrocatechols and tert-butylhydroperoxide, deeper oxidation leads to the formation, in a small amount, of the cleavage products of the aromatic ring; oxalic acid was identified here.…”
Section: Resultsmentioning
confidence: 99%